THE IMPACT OF TERRORIST ATTACKS ON STOCK RETURN AND TRADING VOLUME ACTIVITY IN LQ 45 COMPANY DURING SARINAH ATTACK - Andzela, Maya (Jurnal Manajemen Update, 2018)
Terrorism is not a new issue in recent years. Terrorism is a coordinated attacks aimed to arousing the feeling of terror against a group of people. This paper is investigate an event in Sarinah and describe the relationship between news of terrorist attacks and stock returns and the connection to the Trading Volume Activity of companies categorized in LQ 45 with using two comparison of method which are Mean-Adjusted and MarketAdjusted Model with Semi Strong-Form hypothesis of market efficiency with the estimation of the period is t-15 and t+15. Based on the result, with using Mean-Adjusted and Market Adjusted model, there is no impact of Sarinah Attack on stock return of LQ 45 company. With using Paired Sample Test, there is no impact on Sarinah Attack to the Trading Volume Activity. The next researcher can use another case beside terrorist attack to measure the power of market against some issues in the world.